Explore - Callery,Sean; Gifford,Clive (Kingfisher: UK, 2008)
This amazing universe-in-a-book is the perfect reference for home, school, or anywhere there is a question to be explored. Arranged thematically into ten core subjects, the concise text is clear, accurate, and easy to access. Designed with today's Web-savvy readers in mind, the eye-popping special effects on the cover will attract curious readers. Inside, the information on each page is enhanced by dynamic digital illustrations, the latest photography, step-by-step sequences, and plenty of interesting sidebars. No matter if the question is about the ancient past or technology that will take humankind into the future, young researchers will find the definitive answer here.
Keywords: Children's nonfiction, Science